Rewind for Posttraumatic Stress Disorder: A Randomised Controlled Trial - Astill Wright, Laurence; Barawi, Kali; Kitchiner, Neil; Kitney, Danielle; Lewis, Catrin; Roberts, Alice; Roberts, Neil P.; Simon, Natalie; Ariti, Cono; Nussey, Ian; Muss, David; Bisson, Jonathan I. (Depression and Anxiety, 2023)
Background. The Rewind Technique (Rewind) is a psychological therapy for people with posttraumatic stress disorder (PTSD), which is already used regularly in the National Health Service (NHS), the third sector and private practice across the UK. This study set out to explore the potential efficacy and feasibility of remotely delivered Rewind for the treatment of PTSD. Methods. This study was a two-armed, exploratory RCT to assess the preliminary efficacy, adherence, feasibility, and factors affecting outcome of Rewind versus a waitlist control group. Results. The entire trial was delivered remotely using video calls for treatment sessions and outcome assessments. A total of 40 participants were randomised with 80% retention at the primary endpoint of 8-week postrandomisation. The difference in Clinician-Administered PTSD Scale for DSM-5 scores between the immediate and delayed Rewind arms was 12.64 (95% CI, 2.29 to 22.99, F=6.38, df=1, p=0.02) at 8 weeks. The Cohen’s d was 1.05 indicating a large effect size at 8 weeks with maintenance in symptom improvement at 16 weeks. Conclusion. Rewind, delivered remotely, demonstrated a large effect size in treating symptoms of PTSD within this trial cohort. This trial demonstrates a preliminary signal of efficacy supporting the clinical use of Rewind in the treatment of people with PTSD.